Influência do comprimento e geometria de pinos de fibra de vidro no comportamento biomecânico de incisivos centrais superiores tratados endodonticamente : uma análise pelo método de elementos finitos - Melo, Hosana Aída Silva (2017)
The rehabilitation of endodontically treated teeth represents a challenge for dentistry and is the object of researches that investigastes the physical, chemical and biomechanical properties existing between vital and non-vital teeth and thus indicate the restorative complex that is esthetically acceptable, with adequate clinical function and longevity. For the restoration of these teeth when they have extensive structural loss, the fiber glass posts were introduced as an alternative to metal retainers. The objective of this study was to evaluate the influence of the length and geometry of fiber glass posts (PFV) on the biomechanical behavior of endodontically treated maxillary central incisor under a load of 100 N applied at 130 ° to the palatal surface under the following conditions: (PVF), serrated (S), with depths of 5mm and 10mm. The different forms of treatment were simulated from the three dimensional computational model of a sound maxillary central incisor and analyzed qualitatively through the finite element method. The results were evaluated by von Mises criteria and maximum principal stress. The models PFVL5mm, PFVL10mm and PFVS5mm presented a displacement in the range of 0.0458mm to 0.512mm, while in the PFVS10mm model, this displacement was 0.0116. The smooth glass fiber post had a homogeneous stress distribution, while the serrated post had a stress concentration at the interface of the serrated geometry. The distribution pattern in fiber glass post models was similar to that of the healthy tooth, but the restored models with pins of longer lengths resulted in a more uniform stress gradient with a larger distribution area. The obtained results indicated that fiber glass post of serrated geometry, in greater depth, influences in the reduction of the displacement of the model. In addition, the geometry of the glass fiber post influences the concentration of stresses along the post and increasing the depth of these posts increases the area of distribution of the stress so that they become more homogeneous.